Autophagy regulates MK-2206-induced LDL receptor expression and cholesterol efflux pathways - Hilde Sundvold; Thea Bismo Strøm (PLoS ONE, 2025)
Background Hypercholesterolemia remains a key risk factor for atherosclerotic cardiovascular disease (CVD). The clearance of low-density lipoprotein (LDL) particles from plasma, primarily mediated by LDL receptor (LDLR) activity, is an established target of lipid-lowering therapies. Enhancing reverse cholesterol transport via high-density lipoprotein and modulating cholesterol efflux from macrophages further complements atherogenic risk reduction. Enhancing LDLR expression and supporting effective cholesterol efflux via ATP binding cassette subfamily A member 1 (ABCA1) are therefore essential therapeutic targets for CVD prevention. Recent studies implicate autophagy in lipid and cholesterol metabolism. This study examines the influence of autophagy on LDLR and ABCA1 expression in hepatocytes after treatment with the AKT inhibitors MK-2206 and triciribine. Methods Autophagy was disrupted pharmacologically using SBI-0206965 and genetically via short-interfering RNA (siRNA) targeting autophagy-related genes ATG5 and ATG7 in HepG2. Stable knockout (KO) HAP1 cell lines for ATG5 and ATG7 were generated by CRISPR to ensure complete abrogation of autophagy. The possible effect of SREBP2 silencing on MK-2206-induced LDLR expression was assessed in HepG2 cells. Quantitative analyses included measurement of ABCA1, LDLR and MAP1LC3B (LC3B) expression at protein and mRNA levels, in addition to ULK1 and SQSTM1 ( p62 ) mRNA levels. Results MK-2206 administration increased hepatic LDLR and the autophagy marker LC3B. Triciribine did not show evidence of autophagy induction, and neither AKT inhibitors modified ABCA1 expression. Inhibition of autophagy, either by SBI-0206965 or by siRNA targeting ATG5 and ATG7, reduced the MK-2206-mediated LDLR upregulation by approximately 50% in HepG2. In KO-ATG5/ATG7 HAP1 cells, the MK-2206-induced LDLR expression decreased by 70% compared to wild-type cells, and ABCA1 expression was abolished. Conclusion Both pharmacological and genetic impairment of autophagy attenuate the LDLR-inducing effects of MK-2206, supporting a role for autophagy in the regulation of cholesterol metabolism. The substantial reduction of ABCA1 expression in autophagy-deficient cells further indicates that autophagy is involved in cholesterol efflux regulation.